Pripovedna proza v reviji Vesna - Grčar, Irena (Jezik in slovstvo, 1998)
The literary genre of short story is related to the poetologic orientation of the Vesna, which supported to be a magazine for the demanding reader. When its categorial properties are identified, it is found to differ significantly from the story. Short stories in the Vesna tend to embrace contemporary narrative patterns and the new Romanticism style.
Keywords: Slovene literature; slovenska književnost; slovenske revije; Vesna; 1892/1894